EPISTEMOLOGY OF ISTINBAȚ IN QURAISH SHIHAB’S INTERPRETATION OF MARRIAGE VERSES IN TAFSIR AL-MISBAH - Ishaq, Zamroni; Idri, Idri; Musyafa'ah, Suqiyah; Khalqi, Ahmad Muhammad Sa'dul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Quraish Shihab is a prominent figure in contemporary Islamic scholarship, especially regarding Quranic exegesis. However, some critics challenge his legal formulations concerning marriage law. This study examines Shihab’s istinbâț epistemology—his methodology in deriving Islamic legal rulings— through his marriage-related verses interpretation in Tafsir al-Misbah using Yusuf al-Qaradâwî’s ijtihad theory, the analytical framework. It adopts a qualitative textual approach, focusing on Shihab’s interpretations’ sources, methods, and legal characteristics. The findings reveal Shihab’s diverse sources: Quranic exegesis, asbâb al-nuzûl, Hadith, early scholars’ opinions, and insights from social sciences and health disciplines. He combines ijtihâd intiqâ’î (selective reasoning) and ijtihâd jâmi’ (synthetic reasoning), engaging classical jurisprudence while constructing rulings suited to contemporary contexts. Rationality, contextuality, and flexibility, which mark a shift from rigid traditionalism to an adaptive, ethically driven Islamic legal thought, have characterized Shihab’s legal reasoning. His model affirms that Islamic law must remain faithful to its scriptural foundations while being responsive to modern human realities. This study contributes to the ongoing discourse on legal reform and Islamic epistemology by demonstrating how contextual ijtihâd enriches modern jurisprudence. It highlights the need for dynamic interpretive models bridging tradition and contemporary social change offering valuable insights for scholars, jurists, and reform-oriented Muslim communities.